2021
DOI: 10.1371/journal.pone.0252018
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physician perspectives on screening for axial spondyloarthritis: A qualitative study

Abstract: Background Many patients with axial spondylarthritis (axSpA) experience lengthy diagnostic delays upwards of 14 years. (5–14 years). Screening tools for axSpA have been proposed for use in primary care settings, but whether this approach could be implemented into busy primary care settings remains unknown. Objective To solicit feedback from primary care physicians regarding questions from the Inflammatory Back Pain Assessment: the Assessment of Spondyloarthritis International Society (ASAS) Expert Criteria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…In addition, the proposed screening questions were informed by our previous work in which we explored issues related to patients' diagnostic journeys using evidence-based qualitative research methodology. This helped us to understand and incorporate patient and physician perspectives [15,17,45]. Our study also has several limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the proposed screening questions were informed by our previous work in which we explored issues related to patients' diagnostic journeys using evidence-based qualitative research methodology. This helped us to understand and incorporate patient and physician perspectives [15,17,45]. Our study also has several limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The primary goal of this study was to develop a patient-friendly screener that reflects patient experiences. Considering the complexity of the US healthcare system and the challenges associated with implementation of a screening tool in primary care settings [15,46], evidence to ensure its usefulness in routine primary care practice will be important. In our previous work, we demonstrated that the proposed screener possesses the necessary properties to serve as an effective screening tool: it is brief, understandable at a grade 8 reading level, and can be self-administered [17].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations